2019
DOI: 10.1111/jocd.12921
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of shell of Camellia oleifera Abel extract on mushroom tyrosinase and human skin melanin

Abstract: Summary Background As an oil production byproducts, the shell of Camellia oleifera Abel (SC) is usually discarded in the dump. However, previous investigations suggested that the SC could provide valuable bioactive materials. Objective The objectives of this study were to examine the ability of SC extract to inhibit in vitro tyrosinase activity and the melanin inhibition effects of cosmetic formulations containing SC 1,3‐butanediol extract in human volunteers. Methods The cell viability was determined using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 15 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…Tyrosinase inhibition [125] Ferulic acid Phoenix dactylifera L. seed extract Inhibition of melanin production in B16F10 melanoma cells [126] Phenolic glycoside (gastrodin) Grammatophyllum speciosum pseudobulb extract Inhibition of melanin synthesis [127] Flavonoids, polyphenols, glycans, reducing sugars, chlorogenic acids…”
Section: Camellia Oleifera Abel Shell Extractsmentioning
confidence: 99%
“…Tyrosinase inhibition [125] Ferulic acid Phoenix dactylifera L. seed extract Inhibition of melanin production in B16F10 melanoma cells [126] Phenolic glycoside (gastrodin) Grammatophyllum speciosum pseudobulb extract Inhibition of melanin synthesis [127] Flavonoids, polyphenols, glycans, reducing sugars, chlorogenic acids…”
Section: Camellia Oleifera Abel Shell Extractsmentioning
confidence: 99%
“…The results showed that the 1,3-butanediol extract has the highest tyrosinase inhibition rate of 71.9%, compared to those of the methanol extract (49.2%) and water extract (39.3%). Kojic acid was used as the positive control in this study …”
Section: Biological Activitiesmentioning
confidence: 99%
“…Previous studies have examined the ability of camellia shell extract to inhibit tyrosinase activity in vitro as well as the melanin inhibition of a cosmetic formula containing the extract in 30 female subjects. Camellia shell extract has been used as a skin whitening agent in cosmetic products ( Liu et al, 2019a ). Hu et al (2015) investigated the resistance of camellia shell to fungi and termites; the shells appeared to be toxic to fungi and termites but did not completely eradicate them ( Figure 4 ).…”
Section: Utilization Of C Oleifera Shellmentioning
confidence: 99%